2011
DOI: 10.1038/bjc.2011.75
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional transcription factor TFII-I is an activator of BRCA1 function

Abstract: Background:The TFII-I is a multifunctional transcriptional factor known to bind specifically to several DNA sequence elements and to mediate growth factor signalling. A microdeletion at the chromosomal location 7q11.23 encoding TFII-I and the related family of transcription factors may result in the onset of Williams–Beuren syndrome, an autosomal dominant genetic disorder characterised by a unique cognitive profile, diabetes, hypertension, anxiety, and craniofacial defects. Hereditary breast and ovarian cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…A recent report indeed connects the two proteins by showing that TFII-I directly interacts with BRCA1 via the BRCT domain of the latter (Tanikawa et al, 2011). This study shows that BRCA1 acts as a transcriptional co-factor for TFII-I and activates the expression of several target genes including SIRT1 and tumor suppressor p53 that are involved in DNA damage checkpoint pathways.…”
Section: Structural Properties Of Tfii-imentioning
confidence: 98%
“…A recent report indeed connects the two proteins by showing that TFII-I directly interacts with BRCA1 via the BRCT domain of the latter (Tanikawa et al, 2011). This study shows that BRCA1 acts as a transcriptional co-factor for TFII-I and activates the expression of several target genes including SIRT1 and tumor suppressor p53 that are involved in DNA damage checkpoint pathways.…”
Section: Structural Properties Of Tfii-imentioning
confidence: 98%
“…We found that TF promoter harbors binding sites for some transcription factors already involved in cell growth, proliferation, and cancer-related signaling events. These included TCF-4E, GATA-1, TFII-I, PXR-1:RXR-␣, c-ETS-1, or AP-1/c-Jun (37)(38)(39)(40)(41)(42). Similarly, the involvement of both PAK1 and TF in such processes has been well established (13,33).…”
Section: Pak1 Up-regulates the Expression Of Tissuementioning
confidence: 99%
“…Immunocytochemistry was performed as previously described (21). The primary antibodies used were the same as those for western blotting.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%